Usulan Perbaikan Proses Cross Drainage untuk Mempercepat Waktu Proyek Pembangunan Jalan Raya - Shofa, Mohamad Jihan; Listiyana, Lanis; Cahyadi, Dadi (Universitas Serang Raya, 2018)
The success of the project can be judged by the timeliness of the planned target. The problem in the highway project is in the difference between cross drainage age implementation and the age of the project plan that has been set, so that, the project becomes not timely. This research aims to evaluate the critical path of cross drainage project, and what improvements are appropriate in the framework of project acceleration. The Critical Path Method (CPM) method is used to determine the critical path of the cross drainage project activity, from which critical path will be analyzed by using the Fishbone Diagram. Furthermore, borda technique is used to determine the appropriate improvement.